REVERSE ULNAR PARAMETACARPAL ARTERY FLAP FOR SOFT TISSUE DEFECTS OF HAND - Cheema, Saeed Ashraf (Journal of Ayub Medical College Abbottabad, 2010)
Background: Burn injuries and post burn contractures of the little fingers and areas around are quite common. Release of these contractures may lead to full thickness soft tissue defects which need soft tissue cover. Similarly, mechanical trauma and also road traffic accidents, quite often lead to soft tissue defects of hand. Objective of this study was to evaluate the role of reverse ulnar parametacarpal artery flap in providing soft tissue cover for various full thickness soft tissue defects at the base of little finger and adjacent areas on palmar and dorsal aspects. Methods: It was an observational study, conducted at Department of Plastic Surgery, Services Hospital, Lahore. Study included ten cases with three females and seven male patients. Six of the patients had severe post-burn contractures of little finger, two had the involvement of the adjacent palm areas as well and one case had contracture along the mid palm crease. One case had post mechanical trauma soft tissue defect at dorsal aspect of 4th web space. Contractures were released and resulting soft tissue defects were reconstructed with reverse ulnar parametacarpal artery flap. Age ranged from 9 to 42 years with a mean age of 20.3 years. Results: This flap was utilised in ten cases. All flaps survived, one of the cases developed epidermolysis of whole of the flap which healed uneventfully. Conclusion: Flap is a local option to cover the soft tissue defects of little finger and areas around thus involves the same operative field. Skin texture and features of the donor site also resemble the recipient area. The defect site is closed primarily. Keywords: Contractures, little finger, reconstruction, metacarpal artery flaps